Prarancangan Pabrik Gliserol Dari Crude Palm Oil (CPO) Dan Air Kapasitas 10.000 Ton/Tahun - Pranoto, Heri, Emi Erawati, S.T., M.Eng, Kusmiyati, S.T., M.T., Ph.D (2017)
Glycerol is a required material in various industries, for example: pharmaceuticals, foods, cosmetics, toothpaste, chemical industry, solutions congealed, and printer inks. This glycerol plant is expected to meet the needs of the chemical industry for glycerol, and create new jobs, and can increase local revenue. The glycerol plant is designed with a capacity of 10.000 tons/year. This factory operates continuously for 330 days per year. The process of making glycerol is carried out in the Continuous Stirrer Tank Reactor (CSTR) reactor equipped with heating coils. In reactor the reaction takes place in liquids phase, irreversible, endothermic with operating conditions at 260 °C and at a pressure of 54.28 atm. This plant is classified as high risk due to operating conditions at pressures above atmospheric. This glycerol plant requires raw materials such as Crude Palm Oil (CPO) of 12,097.65 kg/hour and water of 9,678.12 kg/hour. The required utilities are 26,699.35 kg/hour, steam 19,152,31kg/hour, fuel 5,339,28 L/hour, and electricity equal to 389,46 kW. The plant is planned to stand in Rokan Hilir, Riau with an area of 8,545 m2 with a total employee of 132 people. From the results of economic analysis of glycerol plant requires fixed capital (Fixed Capital Cost Investment) of Rp.707.291.902.582,53. Total Manufacturing Cost is Rp.1.048.660.813.140,17. The profit earned before tax amounted to Rp.311.255.124.268,23 while profit after tax of Rp. 217.878.586.987,76. This economic evaluation shows the result, that Percent ROI (Return Of Investment) before tax 44,01%, after tax 30,80%, POT (Payment Out Time) before tax is 1,85 year and after tax 2,45 year. BEP (Break Even Point) 41.12% and SDP (Shut Down Point) of 22.43% and Discounted Cash Flow Rate of Return (DCFRR) 47,2%. The result of the evaluation, said that the Glycerol plant of CPO and water with capacity of 10,000 tons/year is quite feasible to be established.